Green technologies in smart city multifloor manufacturing clusters: A framework for additive manufacturing management - Deja Agnieszka; Ślączka Wojciech; Dzhuguryan Lyudmyla; Dzhuguryan Tygran; Ulewicz Robert (Production Engineering Archives, 2023)
The development of smart sustainable megapolises is associated with the formation of city multifloor manufacturing clusters (CMFMCs) in them directly in the residential area in order to reduce the supply chain from the manufacturer to consumers. Additive technologies (ATs) belong to green technologies because they are considered environmentally sustainable due to less production waste and the ability to reuse of product materials within the circular economy concept. Sustainable development of ATs and additive manufacturing management has become a priority sphere for scientific research, and the use of ATs in the city manufacturing has become any daily reality. Nevertheless, the issues of additive manufacturing management within the CMFMCs have not yet been sufficiently studied. The primary goal of this study was to examine the possibilities of additive manufacturing management in the CMFMCs of the megapolis due to the rational facilities multi-floor layout in production buildings, considering the structure of city manufacturing and business process reengineering related to the needs of the production services market. This paper presents a novel model of facilities multi-floor layout in the production buildings of the CMFMCs, considering the structure of city manufacturing, morphological analysis of the additive manufacturing equipment (AME) used, the balance of material and energy flows under infrastructure capacity limitations of megapolis. The model was verified based on a case study for various options of the floor-by-floor grouping of AME in a building of the CMFMCs. Management solutions for maintaining the flow balance of material, energy and water resources in the CMFMCs are discussed. The results may be useful for additive manufacturing management in an urban environment, taking into account the needs of the production services market in the megapolis.